Understanding Digital Learning Behaviors: Moderating Roles of Goal Setting Behavior and Social Pressure in Large-Scale Open Online Courses - Zhang, Peng (Frontiers in Psychology, 2021)
Pandemic has changed the whole scenario worldwide, not only related to business but also has equally affected the education sector. The classes have gone online from their physical nature, making it more convenient for students to learn. They provide online courses and lectures at the convenience of teachers and students. This study has also been one such effort in identifying the role of technological applications, intentions, and time flexibility in the digital learning behavior of students in China. The sample used in this study was the students taking online courses through their universities. The sample size was 343 students selected through purposive sampling. Smart PLS 3.3.3 has been used for data analysis via structural equation modeling. This study has found that technological applications play an important role in digital learning behavior, positively moderated by goal-setting behavior. Similarly, intentions predict digital learning behavior. Moreover, social pressure has also been found to augment the role of time flexibility in digital learning behavior. These results are very useful for universities that make understanding the online nature of studies more comprehensive.